Isolation and Bioactivity of Natural Products from Streptomyces sp. MA37 - Fleurdeliz Maglangit; Qing Fang; Jioji N. Tabudravu; Kwaku Kyeremeh; Marcel Jaspars; Hai Deng (Molecules)
The isolation and characterization of bioactive metabolites from Streptomyces species continue to represent a vital area of research, given their potential in natural product drug discovery. In this study, we characterize a new siderophore called legonoxamine I, together with a known compound, streptimidone, from the talented soil bacterium Streptomyces sp. MA37, using chromatographic techniques and spectroscopic analysis. Legonoxamine I is a new holo-siderophore, which is likely to be a derailed product from the biosynthetic pathway of legonoxamine A. We also demonstrate that legonoxamine A possesses potent anticancer activity (IC50 = 2.2 µM), exhibiting a remarkable ~30-fold increase in potency against MCF-7 ATCC HTB-22 breast cancer cells compared to desferrioxamine B, a structural analogue of legonoxamine A (IC50 = 61.1 µM). Comparing the structural difference between legonoxamine A and desferrioxamine B, it is deduced that the phenylacetyl moiety in legonoxamine A may have contributed significantly to its enhanced potency. Our findings contribute to the growing library of Streptomyces-derived metabolites and underscore the genus’ potential as a promising source of lead compounds.